Bioethics and Moral Content: National Traditions of Health Care Morality
VI, 306 p.
Keywords: Is there only one bioethics? Is a global bioethics possible? Or, instead, does one encounter a plurality of bioethical approaches shaped by local cultural and national traditions? Some thirty years ago a field of applied ethics emerged under the rubric `bioethics'. Little thought was given at the time to the possibility that this field bore the imprint of a particular American set of moral commitments. This volume explores the plurality of moral perspectives shaping bioethics. It is inspired by Kazumasa Hoshino's critical reflections on the differences in moral perspectives separating Japanese and American bioethics. The essays include contributions from Hong Kong, China, Japan, Texas, the United States, Germany, Switzerland, and Italy. The volume offers a rich perspective of the range of approaches to bioethics. It brings into question whether there is unambiguously one ethics for bioethics to apply.